2016
DOI: 10.1080/10826084.2016.1200097
|View full text |Cite
|
Sign up to set email alerts
|

Should the United States Government Repeal Restrictions on Buprenorphine/Naloxone Treatment?

Abstract: Attention must be focused on needed changes to the current United States law that restricts physicians who prescribe buprenorphine for the detoxification or treatment of Opioid Use Disorder, to accepting no more than100 patients. The current system does not provide comprehensive treatment as defined by the American Society of Addiction Medicine (ASAM) criteria. Additionally, it suffers from both fragmentation and stigma and will require a significant change to comply with ASAM’s call for integrated delivery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…Although academic researchers and public health officials have advocated that OUD be treated with MAT (Volkow et al, 2014; Blum et al, 2016), the current study suggests individuals engaging in non-medical prescription opioid use are interested in a range of treatment options that often include non-MAT care. Yet each form of treatment has inherent practical barriers; for instance, less than 10% of participants in the current study knew whether their insurance covered residential or inpatient detoxifications, despite the fact they were among the highest rated treatments for perceived effectiveness (Table 2; Supplemental Table 4 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although academic researchers and public health officials have advocated that OUD be treated with MAT (Volkow et al, 2014; Blum et al, 2016), the current study suggests individuals engaging in non-medical prescription opioid use are interested in a range of treatment options that often include non-MAT care. Yet each form of treatment has inherent practical barriers; for instance, less than 10% of participants in the current study knew whether their insurance covered residential or inpatient detoxifications, despite the fact they were among the highest rated treatments for perceived effectiveness (Table 2; Supplemental Table 4 ).…”
Section: Discussionmentioning
confidence: 91%
“…Misuse of prescription opioids has led to increased prevalence of opioid use disorder (OUD) (Dart et al, 2015; Jones, 2017) and opioid-related deaths (National Center for Health Statistics et al, 2015; Compton et al, 2016; Braden et al, 2017). In response to the opioid epidemic, scientific and medical communities have advocated for increased availability of evidence-based, pharmacotherapeutic approaches that have been empirically shown to mitigate the incidence of opioid related death and disease transmission (Volkow et al, 2014; Blum et al, 2016) (Volkow et al, 2014; Blum et al, 2016). Pharmacotherapeutic options for OUD treatment, often referred to as medication-assisted treatments (MATs), include opioid agonist/partial agonist maintenance treatments to manage opioid withdrawal and cravings such as buprenorphine (Ling et al, 1998) and methadone (Sees et al, 2000), or opioid antagonist treatment to decrease relapse potential such as oral or extended-release (XR) injectable naltrexone (Krupitsky et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The relatively low numbers of civilian SAT facilities reporting the availability of buprenorphine therapy is concerning, given research which suggests that drug-free treatments may contribute towards greater patient mortality than medication-assisted therapy [33]. Though buprenorphine prescription has, to date, been strictly limited by law, researchers have called on lawmakers to consider relaxing such restrictions as they may contribute to greater patient harm [34]. Previous research has found a similar trend regarding the supply of waivered physicians in the northeast relative to other regions [35] and though some have offered explanations for this with respect to health care reform [36] or regional variations in opioid mortality [37], more research is needed to better understand the factors which have led to the relatively low uptake of buprenorphine treatment outside of the northeast.…”
Section: Discussionmentioning
confidence: 99%
“…These clinically relevant results, with limitations, showing a significant reduction of illicit opioid use and strong compliance, should further encourage the cautious continued and expanded utilization of to bup/nal (Blum, Gold, Clark, Dushaj, & Badgaiyan, 2016). Meanwhile, the long-term use of bup/nal, because of the potential for addiction liability and antireward effects, requires further intensive investigation (Elman et al, 2013;Hill et al, 2013).…”
Section: Resultsmentioning
confidence: 99%